Has the inflation process changed? Selective review of recent research on inflation dynamics - Oleksiy Kryvtsov; James MacGee (Bank of Canada, 2020)
For most of 2011-19, inflation in Canada and advanced economies registered below inflation targets. This has spurred a debate on whether "lowflation" is a temporary phenomenon or rather a sign of a fundamental change in inflation behaviour-in Canada and globally. So far, we know little. Global factors-changes in the price of oil and shifts in trade due to globalization-can only explain a portion of the fluctuations in domestic inflation. Emerging survey data are showing that inflation expectations of managers and households behave very differently from model expectations based on full information and rational behaviour. Recent surveys using randomized control trials reveal that changes in monetary or fiscal policies may lead to unexpected responses of inflation expectations and firm behaviour. Changes in the markets for consumer goods raise the need for us to rethink the methods for measuring inflation. We discuss the questions that these observations bring up for central bankers.
Keywords: E31; E52; 330; Central bank research; Inflation and prices; Monetary policy